Clustering methods for base station cooperation - Jian Zhao; Zhongding Lei (2012 IEEE Wireless Communications and Networking Conference (WCNC), 2012)
When the joint processing technique is applied in the coordinated multipoint (CoMP) transmission downlink, the user data for each mobile station (MS) needs to be distributed among multiple base stations (BSs), which incurs the exchange of user data via the backhaul. In order to alleviate the requirement on the backhaul capacity, we propose to minimize the exchange of user data among the BSs, subject to certain QoS requirements and power constraints. We formulate this problem into an l 0 -"norm" minimization problem, and propose two heuristic methods to solve it. Simulations show that both methods can significantly reduce the data exchange among BSs in the backhaul, only at the cost of marginal increase in the sum transmit power at the BSs.